The material points is massed by springs, found the second law of Newton for every point.

I already do this for one point


And get

$ \begin{cases} m\ddot{x}= -cx - u\cos{a} \\ m\ddot{y}=-cy - u \sin{a} \end{cases}$

Where $c$ - elasticity (same for all springs), $a$ - angle between force and OX ($m\ddot{x}$) and OY ($m\ddot{y}$)

But how to do this for


I try do this, and get (but this is wrong I think)

$ \begin{cases} m\ddot{x_{1}}= -cx + 2u\cos{a} \\ m\ddot{y_{1}}=-cy + 2u \sin{a} \\ m\ddot{x_{2}}= -cx + 2u\cos{a} \\ m\ddot{y_{2}}=-cy + 2u \sin{a} \\ m\ddot{x_{3}}= -cx + 2u\cos{a} \\ m\ddot{y_{3}}=-cy + 2u \sin{a} \\ m\ddot{x_{4}}= -cx + 2u\cos{a} \\ m\ddot{y_{4}}=-cy + 2u \sin{a} \end{cases}$

  • $\begingroup$ hint: you have better and put everything into matrix form $\endgroup$ – G Cab May 15 '18 at 14:05

For the first we have $u(t)=(x(t),y(t))$ thus

\begin{cases} m\ddot{x}= -cx \\ m\ddot{y}=-cy \end{cases}

For the second case we have $4\times2$ degrees of freedom $u_i(t)=(x_i(t),y_i(t))$ and we need to write down the equation of motion accordigly taking into account the relative displacement for the spring connecting two masses and also for the forces $F_i$.

For example for the mass $m_1$, assuming the spring constant "c" for the springs and an angle of 45° for the inclined spring, we have

$$\begin{cases} m_1\ddot{x_1}= -c(x_1-x_3)-c\frac{\sqrt2}2x_1+\frac{\sqrt2}2F_1 \\ m_1\ddot{y_1}= -c(y_1-y_4)-c\frac{\sqrt2}2y_1+\frac{\sqrt2}2F_1\end{cases}$$

for the mass $m_2$ we have

$$\begin{cases} m_2\ddot{x_2}= -c(x_2-x_4)-cx_2+\frac{\sqrt2}2F_2 \\ m_2\ddot{y_2}= -c(y_2-y_3)-cy_2-\frac{\sqrt2}2F_2\end{cases}$$

  • $\begingroup$ Show example for $x_{2}$ please 🙏 $\endgroup$ – Stepan Vanzuriak May 15 '18 at 14:16
  • $\begingroup$ @StepanVanzuriak I've added also the equations for mass $m_2$ and corrected some typo. Try to understand the idea behind and how to obtain the equation. You need to consider for the masses 4 displacement in x direction (right direction) and 4 displacement in y direction (up direction). Then write down the Newton's equation accordingly. $\endgroup$ – gimusi May 15 '18 at 14:23
  • $\begingroup$ In $m_1\ddot{y_1}= -c(y_1-y_3)-c\frac{\sqrt2}2y_1+\frac{\sqrt2}2F_1$, is there must be $y_3$ or $y_4$? $\endgroup$ – Stepan Vanzuriak May 15 '18 at 14:32
  • $\begingroup$ @StepanVanzuriak Yes it is a typo of course, in vertical direction $m_1$ is affected only by $y_4$. I fix. $\endgroup$ – gimusi May 15 '18 at 14:48

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.